Evaluation of the use of the polyubiquitin genes, Ubi4 and Ubi10 as reference genes for expression studies in Brachypodium distachyon. - John P Chambers (Public Library of Science (PLoS), 2012)
Background Brachypodium distachyon is emerging as the model plant for temperate grass research and the genome of the community line Bd21 has been sequenced. Additionally, techniques have been developed for Agrobacterium-mediated transformation for the generation of T-DNA insertional lines. Recently, it was reported that expression of the polyubiquitin genes, Ubi4 and Ubi10 are stable in different tissues and growth hormone-treated plant samples, leading to the conclusion that both Ubi4 and Ubi10 are good reference genes for normalization of gene expression data using real-time, quantitative PCR (qPCR). Principal findings Mining of the Joint Genome Institute (JGI) 8X Brachypodium distachyon genome assembly showed that Ubi4 and Ubi10 share a high level of sequence identity (89%), and in silico analyses of the sequences of Ubi4 (Bradi3g04730) and Ubi10 (Bradi1g32860) showed that the primers used previously exhibit multiple binding sites within the coding sequences arising from the presence of tandem repeats of the coding regions. This can potentially result in over-estimation of steady-state levels of Ubi4 and Ubi10. Additionally, due to the high level of sequence identity between both genes, primers used previously for amplification of Ubi4 can bind to Ubi10 and vice versa, resulting in the formation of non-specific amplification products. Conclusions The results from this study indicate that the primers used previously were not sufficiently robust and specific. Additionally, their use would result in over-estimation of the steady-state expression levels of Ubi4. Our results question the validity of using the previously proposed primer sets for qPCR amplification of Ubi4 and Ubi10. We demonstrate that primers designed to target the 3'-UTRs of Ubi4 and Ubi10 are better suited for real-time normalization of steady-state expression levels in Brachypodium distachyon.